Silymarin, Olibanum, and Nettle, A Mixed Herbal Formulation in the Treatment of Type II Diabetes: A Randomized, Double-Blind, Placebo-Controlled, Clinical Trial - Nahid Khalili MD; Reza Fereydoonzadeh MD; Reza Mohtashami MD; Saeed Mehrzadi PhD; Mojtaba Heydari PhD; Hasan Fallah Huseini PhD (SAGE Publishing, 2017)
Silybum marianum (L) Gaertn (milk thistle) seeds, Urtica dioica L (nettle) leaves, and Boswellia serrata (olibanum gum) resin are used traditionally by Iranian diabetic patients. The aim of this study was to evaluate the antihyperglycemic effects of these herbs in an herbal formulation in patients with type II diabetes mellitus. Sixty patients diagnosed as type II diabetes mellitus with fasting blood glucose level from 150 to 180 mg/dL, glycosylated hemoglobin level from 7.5% to 8.5%, and on oral antihyperglycemic drugs, were allocated to receive the mix herbal formulation or placebo for 90 days in a double-blind randomized placebo-controlled clinical trial. The mean serum fasting blood glucose, glycosylated hemoglobin, and triglyceride in the herbal drug group were significantly less than placebo group's values after 3 months of the intervention. The study showed a potential antihyperglycemic and triglyceride lowering effect of the herbal formulation, while it did not have any significant cholesterol or blood pressure lowering effect.